Analysis of the dynamics of international trade operations in the market of vegetables and fruits in Russia - I. A. Aksenov (Овощи России, 2020)
Relevance. The structure of the food market is represented by various types of products, of which the largest share is taken by the fruit and vegetable sector. In the conditions of a tense political situation in the world and the establishment of barriers in foreign trade, agriculture is a strategically important branch of the Russian economy. Today, the fruit and vegetable sector of the Russian economy does not fully satisfy the needs of the population for vegetables and fruits. This is evidenced by the fact that the domestic market does not provide the population with high-quality vegetables and fruits, creates favorable conditions for filling it with foreign goods, which constitute about 35% of the consumer basket of Russians. All this leads to the need for additional analysis to identify trends in the development of the Russian market for fruits and vegetables and to identify priority areas for its development.Methods. The purpose of the article is to conduct an analysis of the main trends in the development of the Russian fruit and vegetable market, in order to determine the priority areas of its operation. The basis of the study was the statistical data of the customs authorities of the Russian Federation on the import and export of fruits and vegetables, as well as the federal service of state statistics on the volumes of production and consumption of fruits and vegetables in Russia.Results. As a result of the analysis of the state of the fruit and vegetable market in Russia in 2011-2018, carried out in the article. It can be stated that the population is experiencing a shortage of consumption of fruits and vegetables. Over the past eight years, imports exceeded exports in the structure of commodity circulation of fruits and vegetables, which indicates the dependence of the national market on foreign goods. The state of the fruit and vegetable market is influenced by the following factors: the level of development of the logistics infrastructure, material and technical equipment of enterprises, as well as the presence of sanctions and counter sanctions.